Analysis of the determinants of poverty in South Africa - Kgaphola, Hlali Kemedi (My University, 2016)
This research dissertation investigates what factors drive poverty in South Africa using annual data from 1996 to 2013. In an attempt to contribute towards a better understanding of what contributes to poverty in South Africa, the researcher adopted three types of research questions: a contextual research question, a main research question and an applied research question. The central questions of this study was “what drives poverty in South Africa?” and “how do these drivers influence poverty trends in South Africa?” The study recognises poverty as a multi-dimensional phenomenon, in addition to the unidimensional money-metric definition of poverty for analysis purposes. Consequently although the study adopts the monetary definition of poverty as a framework to poverty analysis; it also incorporates other variables that capture the multi-dimensional nature of poverty relevant to the South African context. The study uses various data analysis tools including descriptive statistics, line graphs, bivariate analysis, and trend analysis to investigate the relationship between poverty and the variables in this study. Consistent with Klasen (2000) and Finn et al. (2013), the main findings were that there is a negative relationship between poverty and government expenditure on health, housing, energy, public order and safety, and access to credit in South Africa. On the contrary, government expenditure on education is found not to reduce poverty in South Africa, neither is unemployment found to increase poverty in South Africa. The research concluded that although certain variables are expected to reduce or increase poverty, remedial policy interventions by Government and country specific economic structure mitigate these a prior expectations. From these findings the researcher makes recommendations, contributing to how scholars (and government) can further their attempt to alleviate poverty in South Africa.
A research dissertation submitted in partial fulfilment of a Master of Management in Public Policy (MMPP) The University of Witwatersrand Wits School of Governance 26 February 2015
Keywords: Poverty--South Africa; Poor--South Africa; South Africa--Economic conditions